PENINGKATAN HASIL BELAJAR SISWA MENGGUNAKAN MEDIA PEMBELAJARAN BERBASIS KONTEKSTUAL DI SMP NUSANTARA INDAH SINTANG - Odin, Yohanes Jefritianus; Relita, Dessy Triana; Yulia Suriyanti, Yulia (STKIP Persada Khatulistiwa Sintang, 2024)
The problem in this research is that students are less active in learning, student learning outcomes are low, and students need help to answer questions asked by the teacher, which results in student scores not reaching the minimum completeness criteria (KKM). This research aims to clearly understand the improvement in student learning outcomes by using contextual-based learning media in social studies subjects for class VIII at SMP Nusantara Indah Sintang for the 2023/2024 academic year, with as many as 13 students. The method used in this research is a qualitative descriptive method in the form of PTK classroom action research. Data collection techniques and tools used in this research were observation, interviews, documentation, and tests. The research results showed that the classical value for cycle I was 46.16% and cycle II 92.30%, increasing by 46.14%, while the average value for cycle I was 67.69 and the average value for cycle II was 87.69, rising to 20.00. Thus, students' mastery of the material on advantages and limitations between spaces in demand and supply has increased from medium to high. This means that the use of contextual-based learning media in integrated social sciences learning activities has been proven. Besides that, students' interest in learning shows increased results through students' attention, discipline, activeness, and responsibility in participating in learning, and students can respect their friends well.